Konsep Etika Dan Moralitas Sebagai Materi Dalam Pembelajaran Pendidikan Agama Islam - Hayatunnisa Hayatunnisa; Jenika Fejrin; Milki Salwa Nor Azizah; Muhamad Ilham; Wayan Gastiadirrijal; Syahidin Syahidin; Muhamad Parhan (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
Islamic Religious Education is an important element in the development of individual Muslim character. In this context, the concepts of ethics and morality play a central role in learning Islamic Religious Education. This article raises the urgency of integrating the concepts of ethics and morality in the Islamic Religious Education curriculum. Ethics and morality involve principles that govern human behavior, including values such as justice, kindness, compassion, honesty, and integrity in the Islamic context. Teaching ethics and morality in the Islamic Religious Education curriculum helps students understand these values and apply them in everyday life. The integration of ethics and morality in religious education shapes students' character and helps them make ethical decisions in various situations. In the long term, this approach also plays a role in shaping behavior in accordance with the teachings of the Islamic religion, contributing to the formation of a better society in accordance with the principles of their religion. Therefore, the concepts of ethics and morality must be the main elements in learning Islamic Religious Education.